Ancestral leadership: Place-based intergenerational leadership. (February 2022) - Kelly, Dara; Nicholson, Amber
This article introduces the notion of ancestral leadership that emerges from intergenerational wisdom at the intersection of people, place and ancestral knowledge. Place is a key component of collective continuity in ancestral leadership that reinforces identity, belonging and intergenerational reciprocity. The findings show that places carry leadership legacies and require ongoing maintenance to ensure genealogies of leadership are available to future generations. Engagement with ancestral leadership and its practical application is not bound to tribal and cultural contexts. By knowing the place of someone's ancestors as a lens into their leadership, one sees structures of accountability that extends beyond culturally bound contexts, and includes their leadership expressed in professional environments. The authors contribute to leadership theory by illuminating how ancestral legacies of leadership continue to inform contemporary generations of leadership and is transmitted intergenerationally within frameworks of genealogy.